Assessment of Rhyzopertha dominica (F.) progeny and feeding damage on rice dried with infrared radiation. (March 2019) - Hampton, Rachel M.; Atungulu, Griffiths G.; Odek, Zephania; Rolland, Virginie; Siebenmorgen, Terry J.; Wilson, Shantae A.; McKay, Tanja
Abstract: Infrared radiation (IR) is a method of drying grains that eliminates insect and microbial pests. It is unknown if IR could cause grains to be more susceptible to insects. Thus, the effects of IR on Rhyzopertha dominica development and feeding damage using long-grain rice varieties, Clearfield XL745 (hybrid) and CL152 (pureline), were examined. Rough rice was dried with three IR intensities: 2.15, 2.83, and 10.84 kW/m 2 . The number of progeny developed, feeding damage, and frass weight after IR-drying were compared with air-drying methods for rough rice and rice milled to brown rice after drying. Since R. dominica develop internally, X-ray technology was used to examine internal progeny and feeding damage. Progeny development and kernel damage appeared to be more affected by fraction (brown rice) than the cultivar of rice or intensity of IR used, with more progeny produced on brown rice than rough rice. An IR intensity of 10.84 kW/m 2 increased the number of overall progeny, the amount of adults, and frass produced on CL152 brown rice. An intensity of 10.84 kW/m 2 also increased the amount of larvae observed for both varieties and fractions. The intensity of 10.84 kW/m 2, under the conditions of this study, is not recommended for drying rice. Highlights: CL152 and XL745 rice varieties were dried with three infrared radiation intensities. X-ray technology was used to detect internal R. dominica development and damage. Brown rice had the greatest impact on the amount of progeny and damage. The highest infrared intensity (10.84 kW/m 2 ) increased overall number of progeny. The amount of frass produced was highest with CL152 brown rice dried at 10.84 kW/m 2